2013
DOI: 10.1002/eji.201343493
|View full text |Cite
|
Sign up to set email alerts
|

IL‐23 protection against Plasmodium berghei infection in mice is partially dependent on IL‐17 from macrophages

Abstract: Although IL-12 is believed to contribute to protective immune responses, the role played by IL-23 (a member of the IL-12 family) in malaria is elusive. Here, we show that IL-23 is produced during infection with Plasmodium berghei NK65. Mice deficient in IL-23 (p19KO) had higher parasitemia and died earlier than wild-type (WT) controls. Interestingly, p19KO mice had lower numbers of IL-17-producing splenic cells than their WT counterparts. Furthermore, mice deficient in IL-17 (17KO) suffered higher parasitemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…We also observed that monocytes were able to produce IL‐17A after the challenge with fungus, and this production was related to Dectin‐1, once the receptor blockage reduced the IL‐17A levels. GM‐CSF activation also led to an increase in IL‐17 production, in agreement with some studies showing the participation of phagocytic cells on IL‐17 production . Recently, it was demonstrated that the most severe form of PCM presents a response characterised by Th2/Th9 cells, whereas the milder and chronic inflammatory response presents a predominance of Th17 cells, with an important participation of Th1 cells .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also observed that monocytes were able to produce IL‐17A after the challenge with fungus, and this production was related to Dectin‐1, once the receptor blockage reduced the IL‐17A levels. GM‐CSF activation also led to an increase in IL‐17 production, in agreement with some studies showing the participation of phagocytic cells on IL‐17 production . Recently, it was demonstrated that the most severe form of PCM presents a response characterised by Th2/Th9 cells, whereas the milder and chronic inflammatory response presents a predominance of Th17 cells, with an important participation of Th1 cells .…”
Section: Discussionsupporting
confidence: 88%
“…GM-CSF activation also led to an increase in IL-17 production, in agreement with some studies showing the participation of phagocytic cells on IL-17 production. [71][72][73][74] Recently, it was demonstrated that the most severe form of PCM presents a response characterised by Th2/Th9 cells, whereas the milder and chronic inflammatory response presents a predominance of Th17 cells, with an important participation of Th1 cells. 75 Besides that, Loures et al 34 demonstrated that Th17 and Tc17 are expanded when induced by DC stimulated with P. brasiliensis due to the cooperation of TRL-4 with Dectin-1 and mannose receptors (MR).…”
Section: Discussionmentioning
confidence: 99%
“…SPMs are mobilized from blood monocytes, whereas LPMs are maintained independently of hematopoiesis (34). Importantly, IL-17 has previously been shown to recruit blood monocytes (46,47), as well as mature macrophages (48)(49)(50) to various tissues; and we have detected high levels of Il17ra selectively on SPMs isolated from ID8-bearing animals. Thus, our work identifies a link between IL-17-secreting γδ T cells and the mobilization/expansion of SPMs in the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, malaria appeared as the major trigger of this IL-17A up-regulation in co-infected patients, given that no relationship between patients’ demographic and clinical variables and the corresponding IL-17A serum level could be identified in this group (nor in any other group). Expansion of IL-17-producing cells (either CD4 +  T cells, CD8 + T cells or macrophages) and related cytokines (IL-17, IL-22 and IL-23) has been observed in P. vivax natural infections [59] as well as P. berghei , P. chabaudi and P. fragile animal models [60-62], where these interleukins have been shown to reduce parasite intensity and protect against fatal outcomes [59-61]. Conversely, a clear role of IL-17 immunity in P. falciparum infections is yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%